Numerical Simulation of CO2 Injection and Extraction Heat Transfer in Complex Fracture Networks - Yuguo Liu; Xiaolong Zhao; Yizhong Zhao; Peng Zhao; Yinghui Zhu; Yi Wu; Xinru He (Energies)
In order to reveal the heat transfer mechanism of CO2 injection and extraction in the fracture network of geothermal reservoir rock, based on the assumption of a dual-media model and considering the characteristics of the rock matrix and the fracture network, the changes in the physical properties of the heat transfer fluid, and the effects of multi-field coupling, a coupled thermo–hydro–mechanical (THM) model of CO2 injection and extraction heat transfer was established. A numerical simulation study was carried out to investigate the evolution of injection and extraction temperature and heat extraction performance under the influence of different factors in the randomly distributed fracture network of the reservoir rock, which has a horizontal slit and a high-angle slit, with CO2 as the heat transfer fluid. The results show that the heat exchange efficiency of reservoir fracture is higher than that of rock matrix; compared with water, the CO2 heat extraction rate is low, and the temperature drop in production wells is small, which is favorable to the long-term exploitation of geothermal reservoirs. if the horizontal distance between the production wells and the injection wells is far and the fracture connectivity is good, the heat exchange is strong and the heat extraction rate is higher; increasing the CO2 injection rate will increase the range of the low-temperature area, reduce the temperature of the production wells, and increase the heat extraction rate in a short period of time; and the heat extraction rate will increase in the later stages. The increase in CO2 injection rate will rapidly increase the range of the low-temperature area in a short time, decrease the temperature of the production well and increase the heat extraction rate, and then the growth of the heat extraction rate tends to stabilize in the later stages; the width ratio of horizontal fracture and high-angle fracture affects the direction of heat exchange, the temperature of production well and the heat extraction rate, and the influence is more significant when the width ratio is greater than 1; the temperature of the production well decreases fastest, the increase in the heat extraction rate is largest, and the effects on the temperature of the production well and the heat extraction rate are insignificant when it is close to the production well. The increase in the heat extraction rate is slower when close to the injection well.